Homosexual and Heterosexual Child Molestation: Case Characteristics and Sentencing Differentials - Walsh, Anthony (International journal of offender therapy and comparative criminology, 1994)
This article compares case characteristics and sentencing differentials of homosexual and heterosexual child molesters. It is asserted that sex offenders are the most despised of all criminals and that among sex offenders none are more despised than homosexual child molesters. The current AIDS scare is viewed as an additional factor exacerbating the general opprobrium attached to homosexual child molesting. Using logit regression, it was found that homosexual molesters were 6.79 times more likely to be imprisoned than were heterosexual molesters qfter adjusting for the combined effects of crime seriousness, prior record, and acceptance/denial of full responsibility for their actions. The latter variable was the only other nonlegal variable to significantly impact sentencing